Experiences of undergraduate university nurse lecturers on the online assessment of the affective domain during covid-19 pandemic in city of Tshwane - Mashao, Kapari Constance (University of Pretoria, 2025)
Dissertation (MNurs (Nursing Science))--University of Pretoria, 2025.